AI morality - Edmonds, David (Oxford University Press, 2024)
A philosophical task force explores how AI is revolutionizing our lives - and what moral problems it might bring, showing us what to be wary of, and what to be hopeful for. There is no more important issue at present than artificial intelligence. AI has begun to penetrate almost every sphere of human activity. It will disrupt our lives entirely. David Edmonds brings together a team of leading philosophers to explore some of the urgent moral concerns we should have about this revolution. The chapters are rich with examples from contemporary society and imaginative projections of the future. The contributors investigate problems we're all aware of, and introduce some that will be new to many readers. They discuss self and identity, health and insurance, politics and manipulation, the environment, work, law, policing, and defence. Each of them explains the issue in a lively and illuminating way, and takes a view about how we should think and act in response. Anyone who is wondering what ethical challenges the future holds for us can start here